ASSESSMENT OF COORDINATION BETWEEN UNITS IN HOSPITAL BY HIGH PERFORMANCE WORK PRACTICES - Sari, Intan Permata; Wulandari, Ratna Dwi (Jurnal Administrasi Kesehatan Indonesia, 2015)
ABSTRACTThe survey about coordination in hospital showed that the coordinaton between units have low score including the lack of communication and problem solving between units. The objectives of this study is to describe coordination in hospital considered by high performance practices that consist of 5 items : selection for cross-functional teamwork, rewards for cross-functional teamwork, cross-functional teamwork conflict resolution, cross-functional meetings, and cross-functional boundary spanner. This research is descriptive study using cross sectional design. Samples or respondents are 16, selected using purposive sampling according to the units which their function and job still related with the medical service in the hospital. The result showed that there are a specific criteria to select their employee. The most responden said that education level is the most important criteria for the selection. There is a reward for the best employee those are trophy and some money given to the best employee and the best group of the months. There is conflict resolution through the meeting with the supervisor and director to discuss their problems. There is functional meeting that is weekly report, and there is boundary spanner to coordinated with the other unit if they have problems. This study conclude that coordination in hospital can complete four items of performance work practice, but aspect cross-functional meetings still not working properly. Therefore, it needs to be repaired because this meeting is important to discuss about development of the medical service in this hospital.Keywords :Coordination, high performance work practices, medical service